Determining the geographical origin of Chinese green tea by linear discriminant analysis of trace metals and rare earth elements: Taking Dongting Biluochun as an example. (January 2016) - Ma, Guicen; Zhang, Yingbin; Zhang, Jianyang; Wang, Guoqing; Chen, Liyan; Zhang, Minglu; Liu, Ting; Liu, Xin; Lu, Chengyin
Abstract: Geographic origin of food is topic of interest for both consumers and producers since the prices of agricultural products can vary greatly according to their geographic origins. Determining the geographic origins of green teas produced in specific regions is very important. Here, we take one of the Chinese famous green teas Dongting Biluochun (DTBLC) as a model to classify its geographic origin based on the metal element analysis combined with the statistical analysis. A total of 37 metal elements including rare earth elements were analyzed by ICP-MS and PCA, CA and LDA were used to describe the relationship of BLC tea profiles from different geographical origins. High recognition (98.2%) and satisfactory predictive ability (96.4%) of the developed LDA model proved that the proposed method is a powerful, practical tool which is suitable for tracing unclassified BLC samples. Moreover, the authentic DTBLC from different protection areas also achieved as high as 95.2% classification rate. Besides, the method of determining the geographic origin of DTBLC was also suitable for other green teas from close regions. Our study provides a high classification rate, good sensitivities and powerful tool to address the quality control and food authenticity concerns regarding green tea which is of great importance for the green tea industry. Highlights: Discrimination of geographic origin of Chinese green tea. Multielement and Multivariate statistical analysis of DTBLC samples. DTBLC from different protection areas achieved high classification rate based on LDA. The established model was suitable for other green teas from close regions.